Kuisin warisan Melayu - Ismail Ahmad, 1960- (Shah Alam, Selangor : Marshall Cavendish Cuisine, 2006)
Mengandungi 72 resepi kuisin masakan melayu asli
Keywords: Cookery, Malaysian; Cookery, Malay; Recipes -- Malaysia